STUDY ON THE ACTION OF PENICILLIN ON M MALLEI AND OTHER BACTERIA - VALDES ORNELAS, OSCAR; MADRAZO, ALICIA (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
A study was made of the action of sublethal doses, as evidenced by blood and marrow counts, of antireticular cytotoxic serum (ACS) applied subcutaneously in guinea pigs The ACS used had a titer in the complement fixation reaction of 1:320 and in the prec
CIENC MEX
Keywords: STUDY, ACTION, PENICILLIN, M MALLEI, OTHER BACTERIA; MULTIDISCIPLINARIA; MICROBIOLOGIA; BACTERIOLOGIA